Changes in Whole-Body Oxygen Consumption and Skeletal Muscle Mitochondria During Linezolid-Induced Lactic Acidosis. Issue 7 (July 2016) - Protti, Alessandro; Ronchi, Dario; Bassi, Gabriele; Fortunato, Francesco; Bordoni, Andreina; Rizzuti, Tommaso; Fumagalli, Roberto
Abstract : Objective: To better clarify the pathogenesis of linezolid-induced lactic acidosis. Design: Case report. Setting: ICU. Patient: A 64-year-old man who died with linezolid-induced lactic acidosis. Interventions: Skeletal muscle was sampled at autopsy to study mitochondrial function. Measurements and Main Results: Lactic acidosis developed during continuous infusion of linezolid while oxygen consumption and oxygen extraction were diminishing from 172 to 52 mL/min/m 2 and from 0.27 to 0.10, respectively. Activities of skeletal muscle respiratory chain complexes I, III, and IV, encoded by nuclear and mitochondrial DNA, were abnormally low, whereas activity of complex II, entirely encoded by nuclear DNA, was not. Protein studies confirmed stoichiometric imbalance between mitochondrial (cytochrome c oxidase subunits 1 and 2) and nuclear (succinate dehydrogenase A) DNA–encoded respiratory chain subunits. These findings were not explained by defects in mitochondrial DNA or transcription. There were no compensatory mitochondrial biogenesis (no induction of nuclear respiratory factor 1 and mitochondrial transcript factor A) or adaptive unfolded protein response (reduced concentration of heat shock proteins 60 and 70). Conclusions: Linezolid-induced lactic acidosis is associated with diminished global oxygen consumption and extraction. These changes reflect selective inhibition of mitochondrial protein synthesis (probably translation) with secondary mitonuclear imbalance. One novel aspect of linezolid toxicity that needs to be confirmed is blunting of reactive mitochondrial biogenesis and unfolded protein response.